Investigating the potential neuroprotective benefits of taurine and Dihydrotestosterone and Hydroxyprogesterone levels in SH-SY5Y cells - Almohaimeed, Hailah M.; Almars, Amany I.; Alsulaimani, Fayez; Basri, Ahmed M.; Althobaiti, Norah A.; Albalaw, Aishah E.; Alsharif, Ifat; Al Abdulmonem, Waleed; Hershan, Almonther Abdullah; Soliman, Mona H. (Frontiers in Aging Neuroscience, 2024)
Background: Taurine, an amino acid abundantly found in the brain and other tissues, has potential neuroprotective properties. Alzheimer's disease (AD) is a commonly occurring type of dementia, which becomes more prevalent as people age. This experiment aimed to assess the neuroprotective effects of taurine on SH-SY5Y cells by examining its impact on Dihydrotestosterone (DHT), Dihydroprogesterone (DHP), as well as the expression of miRNA-21 and miRNA-181.The effects of various taurine concentrations (0.25, and 0.75mg/ml), and LPS (0.1, and 12 mg/ml) on the SH-SY5Y cell line were assessed using the MTT assay. The levels of DHT and DHP were quantified using an ELISA kit. Additionally, the expression levels of miRNA-181 and miRNA-21 genes were examined through Real-Time PCR analysis.The results of the MTT assay showed that treatment with taurine at concentrations of 0.25, and 0.75 mg/ml reduces the toxicity of LPS in SH-SY5Y cells. ELISA results indicated that taurine at a concentration of 0.25, and 0.75 mg/ml significantly elevated DHT and DHP hormones in the SH-SY5Y cell line compared to the untreated group (P<0.01). The expression levels of IL-1β and IL-6 were decreased under the influence of LPS in SH-SY5Y cells after taurine treatment (P< 0.01). Gene expression analysis revealed that increasing taurine concentration resulted in heightened expression of miRNA-181 and miRNA-21, with the most significant increase observed at a concentration of 0.75 mg/ml (p<0.001).Our study findings revealed that the expression of miRNA-181 and miRNA-21 can be enhanced by taurine. Consequently, exploring the targeting of taurine, miRNA-181, and miRNA-21 or considering hormone therapy may offer potential therapeutic approaches for treating AD or alleviating severe symptoms. Nonetheless, in order to fully comprehend the precise mechanisms involved, additional research is required.